2014
DOI: 10.1186/1471-2342-14-14
|View full text |Cite
|
Sign up to set email alerts
|

Sidestream dark field images of the microcirculation: intra-observer reliability and correlation between two semi-quantitative methods for determining flow

Abstract: BackgroundSince analysis of Sidestream Dark Field images still requires subjective interpretation, we wanted to determine intra-observer repeatability and to estimate the correlation between different evaluation methods.MethodsFifty-four Sidestream Dark Field videos were analyzed twice by the same blinded observer using validated software. Vessels were detected, generating the parameter Total Vessel Density (TVD), and flow was determined by (i) classifying each vessel separately, generating the parameters Perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…In keeping with our findings, measures of small vessel density appear to be most related to physiological changes (Alba-Alejandre et al 2013; Nussbaum et al 2014). This is a similar finding to a recent review of sidestream dark-field videomicroscopy that also concluded that the quantitative assessments may be more reliable than some of the indexing methodologies (Petersen et al 2014).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In keeping with our findings, measures of small vessel density appear to be most related to physiological changes (Alba-Alejandre et al 2013; Nussbaum et al 2014). This is a similar finding to a recent review of sidestream dark-field videomicroscopy that also concluded that the quantitative assessments may be more reliable than some of the indexing methodologies (Petersen et al 2014).…”
Section: Discussionsupporting
confidence: 91%
“…This is a similar finding to a recent review of sidestream dark‐field videomicroscopy that also concluded that the quantitative assessments may be more reliable than some of the indexing methodologies (Petersen et al. ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The "vessel-by-vessel" approach to MFI calculation (11,12) was utilized in this study, in which the mean value of the MFIs in each individual vessel is calculated. This approach has been shown to provide the best correlation with both the erythrocyte velocity and the proportion of perfused small vessels (36) and, furthermore, demonstrates the closest intraobserver reliability for vessel detection and flow classification (35).…”
Section: Analysis and Scoring Of Microcirculatory Video Imagesmentioning
confidence: 95%
“…14 The aim of the present study is to assess the safety, feasibility, and efficacy of sidestream darkfield (SDF) microscopy, an advanced imaging technique which meets the above criteria, to investigate the revascularization of ADM, a core component of ADM biointegration, in the context of ADM-assisted breast reconstruction at the time of tissue expander to implant exchange. 14,15 The SDF microscopic image acquisition uses a type of orthogonal polarization spectral imaging, which represents a noninvasive real-time method of imaging the microcirculation in nonkeratinized epithelial surfaces. 16 The SDF image acquisition has been used previously to assess changes in the microcirculation of sublingual mucosa and serosal tissues in the setting of cardiac surgery, thoracic surgery, shock, and systemic inflammatory response syndrome.…”
mentioning
confidence: 99%